Manutenção centrada em confiabilidade visando a competitividade em uma indústria moedora de grãos na região dos Campos Gerais - Silva, Elielson de Bonfim (2018)
Over the last 40 years the maintenance area has undergone a major development modifying its objectives, going from the concept of repair to prevent and / or predict the occurrence of failures. In this context, several systems were created to increase the productivity and competitiveness of the industry. This work has the objective of deepening the knowledge of the maintenance centered in the reliability of the equipment, addressing the advantages in working with the tool of the maintenance centered for the competitiveness in a company in the branch of grain processing.